Important Points of Diagnosis and Treatment Strategy of Intraperitoneal Bladder Perforation due to Blunt Pelvic Trauma in a Pediatric Case - Cansu Kural; Oktay Ulusoy; Emel Ulusoy; Murat Duman (Galenos Yayinevi, 2023)
Intraperitoneal bladder perforation is a vital condition that is characterized by perforation of the bladder into the intra-abdominal area. It can lead to severe peritonitis and a delayed diagnosis can be life-threatening. Bladder perforations are occurred by high-energy blunt trauma that disrupts the bony pelvis, direct blow to a distended bladder, penetrating traumas, urogynecological interventions, indwelling catheters and iatrogenic causes. A 9-year-old boy who was involved in a moderate velocity a motor vehicle accident was referred to our hospital due to pelvic fracture. Primary assessment of the patient suggested hemodynamic stability without any signs of peritonitis and/or distention. With this case report, we aimed to present the clues in the diagnosis of intraperitoneal bladder perforation and our treatment strategy in cases where the symptoms and signs are insufficient to show intraperitoneal bladder perforation.